Impact of Simulated Wildfire Smoke on Potato Growth, Storage and Profitability - Mike Thornton; Owen McDougal; Addie Waxman; Joe Guenthner; Ajay Atkinson (American Journal of Potato Research, 2025)
Potato growers and processors throughout the Pacific Northwest have observed that extensive periods of smoke exposure from summer wildfires can have negative effects on potato crops ( Solanum tuberosum L). Replicated field studies were conducted during 2022 and 2023 to document the impact of smoke exposure on yield, grade and storability of three russet potato cultivars (‘Russet Burbank’, ‘Clearwater Russet’, ‘Alturas’). Potato plants were treated from July 10 to August 18 each year in clear plastic-covered hoop house enclosures between 6:00 and 9:00am MST, before rising temperatures within the enclosures would cause heat stress. The fuel used to generate smoke consisted of a mixture of hard and soft wood tree species. Tubers were harvested in mid-September, graded, and samples placed into storage at 9 o C for 6 months. Yield, quality and decay after storage were used to calculate revenue and smoke impact using a potato processing contract. Potato plants exposed to smoke did not exhibit any visual symptoms and did not senescence earlier than plants not exposed to smoke. Smoke exposure caused a decline in proportion of U.S. No 1 tubers ( p = 0.09). and a slight increase in the proportion of cull tubers ( p = 0.08). The effect of smoke on cull production was more apparent during the 2022 trial when daytime high temperatures were often above the level considered optimum for potato growth, and less apparent in the more moderate conditions experienced during 2023. A similar effect was seen on specific gravity, with smoke treatment causing a significant decline in 2022 but not in 2023. Smoke treatments had no impact on weight loss but decreased decay after six months of storage. The three cultivars tended to exhibit different responses to smoke exposure in terms of proportion of 170 g tubers ( p = 0.06 and 0.04, respectively). Alturas and Russet Burbank exhibited no change in the percentage of 170 g tubers due to smoke treatment in both 2022 and 2023. In contrast, Clearwater Russet showed an increase in 170 g in response to smoke treatment in 2022, but no effect in 2023. The impact of smoke on crop revenue was variable, ranging from a 20% decrease to a 17% increase. It is unclear whether cultivar selection could be used as a tool to reduce the risk of losses due to wildfire smoke exposure.